Evaluation of Fungal Laccase Immobilized on Natural Nanostructured Bacterial Cellulose - Chen, Lin; Zou, Min; Hong, Feng F. (Frontiers in Microbiology, 2015)
The aim of this work was to assess the possibility of using native bacterial nanocellulose (BC) as a carrier for laccase immobilization. BC was synthesized by Gluconacetobacter xylinus, which was statically cultivated in a mannitol-based medium and was freeze-dried to form BC sponge after purification. For the first time, fungal laccase from Trametes versicolor was immobilized on the native nanofibril network-structured BC sponge through physical adsorption and cross-linking with glutaraldehyde. The properties including morphologic and structural features of the BC as well as the immobilized enzyme were thoroughly investigated. It was found that enzyme immobilized by cross-linking exhibited broader pH operation range of high catalytic activity as well as higher running stability compared to free and adsorbed enzyme. Using ABTS as substrate, the optimum pH value was 3.5 for the adsorption-immobilized laccase and 4.0 for the crosslinking-immobilized laccase. The immobilized enzyme retained 69% of the original activity after being recycled seven times. Novel applications of the BC-immobilized enzyme tentatively include active packaging, construction of biosensors, and establishment of bioreactors.